Analisis Teori Belajar Kognitif dan Implikasinya terhadap Efektivitas Pembelajaran di Sekolah Dasar - Norma Kumala Sari; Dwi Agustina Kurniawati; Emna Laisa; Moh. Hawaijul Asrori; Robiatul Adawiyah (STIKes Ibnu Sina Ajibarang, 2026)
This study aims to analyze in-depth cognitive learning theory and its implications for improving the effectiveness of Islamic Religious Education (PAI) teaching at the elementary school level. The adopted methodological approach is qualitative through library research, with the application of content analysis and theoretical synthesis techniques. Primary data sources were obtained from academic literature including textbooks, scientific journals, and the latest empirical research relevant within the last decade. The results of the analysis indicate that cognitive learning theory positions cognitive processes as the core of learning activities, allowing students to function as active agents in constructing knowledge through understanding, analysis, memory representation, and integration with pre-existing cognitive schemas. In the context of PAI, this approach enables meaningful learning through interactive pedagogical strategies such as collaborative discussions, problem-solving, case studies, and metacognitive reflection, which are empirically adapted to the stages of students' cognitive development. The implementation of cognitive theory significantly contributes to strengthening conceptual understanding, increasing learning engagement, developing critical thinking skills, transferring knowledge, and internalizing Islamic values. Thus, cognitive learning theory makes a substantial contribution to optimizing the effectiveness of PAI teaching in elementary schools through an interactive, systematic, and understanding-oriented approach.